The physical demands of professional soccer goalkeepers throughout a week-long competitive microcycle and transiently throughout match-play - White, A.; Hills, S. P.; Hobbs, M.; Cooke, C. B.; Kilduff, L. P.; Cook, C.; Roberts, C.; Russell, M. (Journal of Sports Sciences, 2020)
The physical demands of English Premier League soccer goalkeepers were quantified during training and match-play in a two-part study. Goalkeeper-specific micromechanical electrical systems (MEMS) devices, profiled training and match-day activities throughout one competitive week (n=8; part A). Changes in MEMS-derived outputs were also profiled throughout match-play (100 matches; n=8, 18±14 observations per goalkeeper; part B). In part A, goalkeeping-training elicited the most dives (51±11) versus all activities (all p=0.030) except shooting-training (p=0.069). Small-sided games elicited the fewest (5±3) dives (all p=0.012). High-speed distance covered in match (103±72 m) was similar to goalkeeping-training (p=0.484), while exceeding shooting-training, small-sided games, pre-match shooting, and pre-match warm-up (all p=0.012). Most changes of direction (34±12) and explosive efforts (70±18) occurred during goalkeeping-training, with values exceeding match (both p=0.012). In part B, between-half reductions in total distance, but increased high-speed changes of direction and explosive efforts, occurred (both p=0.05). Excluding the number of high jumps, all variables differed from 0-15-min during at least one match epoch, with more dives (1.3±1.4 vs 1.0±1.1) and explosive efforts (2.5±2.4 vs 2.0±1.8) performed between 75-90-min versus 0-15-min (all p<0.05). These data highlight the differing physical demands of various activities performed by professional soccer goalkeepers throughout a competitive week.